Discretionary sanctions and rewards in the repeated inspection game - Daniele Nosenzo; Theo Offerman; Martin Sefton; Ailko van der Veen (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2012)
We experimentally investigate a repeated "inspection game" where, in the stage game, an employee can either work or shirk and an employer simultaneously chooses to inspect or not inspect. Combined payoffs are maximized when the employee works and the employer does not inspect. However, the unique equilibrium of the stage game is in mixed strategies with positive probabilities of shirking/inspecting. We examine the effects of allowing the employer to sanction or reward the employee after she has inspected the employee. We find that rewards or sanctions can both discourage shirking, and have similar effects on joint earnings. In games allowing sanctions a reduction in shirking is accomplished with a lower inspection rate and the efficiency gains accrue to employers. In games allowing rewards employers actively reward employees for working and the efficiency gains are shared more equitably. A treatment where employers can combine sanctions and rewards leads to efficiencies similar to the single-instrument treatments, and outcomes more closely resemble those of the reward treatment in that the efficiency gains are shared.
Keywords: C70; C72; C92; 330; Inspection Game; Costly Monitoring; Discretionary Incentives; Rewards; Punishment; Experiment